Ownership concentration and firm's performance evidence from the Malaysian exchange / Anita Hasli … [et al.] - Hasli, Anita; Mohd. Ghani, Mohd. Mokhtar; Tuah, Hamri (2004)
This study investigates the effect of ownership structure and concentration on firm's performance. Ownership structure and concentration were determined by observing ownership with regard to identity and ownership with significant variables and the relative importance of each predictor on the performance indicators i.e. firms profitability. Firm's profitability is measured by return on assets, return on capital employed and operating margin. The study involved pooled data over a period of 4 years (1998-2001) with a total of 402 observations extracted from the Malaysian Stock Exchange Berhad. The results showed that 80% of the owners were individual owners, other companies and nominees. There is minimal government, social responsible funds and family involvement in these companies.